Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.celrep.2020.02.100
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A Prevents HIV-1 Restriction in Lymphocytes by Blocking Human TRIM5α Binding to the Viral Core

Abstract: Highlights d Depletion of cyclophilin A (CypA) expression in CD4 + T cells blocks HIV-1 infection d CypA binding to the core prevents HIV-1 restriction by TRIM5a during T cell infection d Endogenously expressed TRIM5a binds to the HIV-1 core and blocks reverse transcription d Human TRIM5a binds to HIV-1 cores but not to cores bearing capsid changes A92E/G94D

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 65 publications
4
98
0
Order By: Relevance
“…Our results showing a requirement for autophagy factors in activation of these same immune pathways in response to TRIM5 over-expression suggested that autophagy factors may also contribute to TRIM5-dependent signaling in response to retroviral capsid. For these studies, we used an HIV-1 mutant with a single amino acid substitution in the capsid protein (P90A) that was recently shown to be strongly restricted by human TRIM5 in primary immune cells [ 29 , 30 ]. Additionally, P90A was previously shown to activate innate immune signaling and interferon expression [ 31 ], but this activity was not connected to TRIM5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showing a requirement for autophagy factors in activation of these same immune pathways in response to TRIM5 over-expression suggested that autophagy factors may also contribute to TRIM5-dependent signaling in response to retroviral capsid. For these studies, we used an HIV-1 mutant with a single amino acid substitution in the capsid protein (P90A) that was recently shown to be strongly restricted by human TRIM5 in primary immune cells [ 29 , 30 ]. Additionally, P90A was previously shown to activate innate immune signaling and interferon expression [ 31 ], but this activity was not connected to TRIM5.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of TRIM5 to transduce antiviral signaling is dependent on its capacity to interact with the intact retroviral core; hence human TRIM5 is activated by N-MLV but not HIV-1. In this study, we showed that an HIV-1 capsid mutant that was recently demonstrated to be bound and restricted by human TRIM5 [ 29 , 30 ] could activate TRIM5-dependent signaling in macrophage-like cells. Importantly, the ability of this virus to stimulate the expression of the key antiviral cytokine interferon β was lost in autophagy-deficient cells, again demonstrating the importance of the autophagy machinery in TRIM5 signaling ( Fig 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…This molecule inhibited HIV with the following CypA-capsid lack of interaction. This is another issue which requires further research in order to explain the role of cyclosporine in HIV infection [41]. The question about its possible role in HIV infection remains open, with some evidence pointing to the possible inhibitory effect of cyclosporine on HIV replication.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…Hepatitis C [15][16][17] Influenza virus infection [28] Rotavirus infection [29,30] Human Immunodeficiency Virus infection [26,33,34] Coronavirus infection [39][40][41][42][43] Hepatitis B [10][11][12][13][14] Hepatitis D [12,20] Herpes simplex infection [26,27] Herpes Zoster Virus infection [35,36] Hepatitis E [21] Cytomegalovirus infection [19,20,22] Human Papilloma Virus infection [29,30] Human Herpesvirus-8 (Kaposi Sarcoma virus) infection [42,43] The possible beneficial effect of cyclosporine on the course of COVID-19 seems very probable. Thus, it is not justified to suggest that patients with autoimmune diseases should discontinue cyclosporine therapy solely because of the COVID-19 pandemic.…”
Section: Possible Negative Effect Of Cyclosporine On Disease Coursementioning
confidence: 99%
“…Disruption of CypA–CA interactions by either treatment with cyclosporine or its analogues (e.g., Debio 025) or by mutation within CA (e.g., G89V or P90A) decreased HIV-1 infection, by affecting uncoating or reverse transcription in certain cell types [ 34 , 35 , 36 , 37 ]. CypA has also been recently found to protect HIV-1 from TRIM5α-mediated restriction in human primary cells [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%